2023
DOI: 10.1037/apl0001032
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of the causal effects of role demands on work–family conflict: A genetic modeling approach.

Abstract: Over the past several decades, there has been considerable interest in the theoretical causes of work-family conflict (WFC). Most studies have focused on situational determinants, often ignoring the role of personal factors such as disposition and heritable elements. We increase understanding of person versus situation influences on WFC through estimation of the relationship between role demands and WFC after controlling for genetic confounding, measured personality traits, family confounds, and other stable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…(2022) found that WFC levels are primarily stable, at least over mid‐ to longer‐term timeframes. Further to the issue of stability, recent work based on genetic modeling found both directions of WFC have additive genetic components (Allen et al., 2022). Research also suggests that individuals may adapt to WFC across time (Matthews et al., 2014) and that there is likely a more dynamic relationship between WFC and wellbeing than assumed by traditional models.…”
Section: Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) found that WFC levels are primarily stable, at least over mid‐ to longer‐term timeframes. Further to the issue of stability, recent work based on genetic modeling found both directions of WFC have additive genetic components (Allen et al., 2022). Research also suggests that individuals may adapt to WFC across time (Matthews et al., 2014) and that there is likely a more dynamic relationship between WFC and wellbeing than assumed by traditional models.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…There is an abundance of research on the predictors and outcomes associated with WFC. Research consistently shows work role demands are robust predictors of WIF and family role demands are robust predictors of FIW (e.g., Allen et al., 2020, 2022; Amstad et al., 2011; Ford et al., 2007; Michel et al., 2011). There is also a strong body of literature that indicates support from others is negatively associated with WFC (French et al., 2018; French & Shockley, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fourthly, researchers highlight the interconnectedness of personal, work, and family domains, with potential positive or negative effects ( Han et al, 2023 ). Excessive work demands deplete employees’ time and energy, leading to work–family conflict (WFC) because more job involvement constrains full engagement in family roles ( Allen et al, 2023 ). Moreover, unfavorable outcomes include decreased well-being and job dissatisfaction ( Carlson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 9 Due to its prevalence and the substantial influence it can have on people’s quality of work and life, 4 there has been considerable academic research on the topic of WFC. 10 , 11 Earlier studies on the consequence of WFC mainly focused on employees’ mental health (eg, general stress and depression, 12 , 13 burnout, 1 , 14 emotional intelligence, and self-efficacy) 15 and physical health (eg, coronary heart disease, 16 hypertension). 17 Recently, research on the impact of WFC has also begun to spill over into the behavioral domain, such as aggressive behavior, 18 procrastination behavior, 19 and workplace deviance behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Since WFC is highly prevalent, 10 exploring the effects of WFC on consumption behavior is not a trivial matter, as it helps advance our overall picture of the possible aftereffects of WFC. Theoretically, our contribution to the study of the work-family interface is to extend the effect of WFC to extra-organizational behavior for the first time.…”
Section: Introductionmentioning
confidence: 99%